Analisis Kualitas Produk Sepeda Motor Honda - Muhamad Jundanila; Nasrulloh Nasrulloh; Syamsul Hidayat (Ebisnis Manajemen, 2024)
The Indonesian economy is currently developing rapidly. One example is the need for motorbikes which are of interest to the public. In the motorbike industry, it is possible for manufacturers to compete with each other by achieving high sales by prioritizing attractive appearance and design in motorbike design, so that consumers are interested in the research method in this research using quantitative methods. The population in the study is the general public who use Honda motorbikes, so they can provide opinions about the quality of Honda motorbikes. In this study, the population is infinite, while the sample taken was 302 respondents. The results of the data analysis above show that there are no differences of opinion on each question, this happens because the data is valid and reliable. What can be concluded is that the opinion of the respondents believes that the quality of Honda motorbikes is very good. The factors in this questionnaire question are quality, influence of quality, performance, durability, specifications, promotion and brand image. Based on research conducted on Honda motorbikes, it can be concluded that product quality, influence of quality, performance, durability, specifications, promotion and brand image has a significant effect on consumer satisfaction. Because good quality can make consumers believe in a product being marketed so that it will attract existing competitors.